Peran Sistem Informasi Akuntansi Dalam Meningkatkan Efisiensi Operasional UMKM - Khoirunnisa (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2025)
This study analyzes the role of Accounting Information Systems (AIS) in improving the operational efficiency of Micro, Small, and Medium-sized Enterprises (MSMEs). Using a qualitative approach with a case study method, this research collected data through in-depth interviews, observations, and document analysis from several MSMEs that have adopted AIS. The findings indicate that AIS implementation has a significant impact, particularly in automating previously manual business processes, which leads to a substantial increase in the speed and accuracy of transaction recording. AIS enables MSMEs to have real-time financial visibility, which is crucial for strategic decision-making. Although challenges such as initial costs and resistance to change exist, the benefits gained—including time savings, improved internal control, and simplified report generation—far outweigh these obstacles. In conclusion, this research suggests that adopting AIS is not just an option but a strategic necessity for MSMEs aiming for growth and sustainability in the digital age.